Fractionation of an anthocyanin-rich bilberry extract and in vitro antioxidative activity testing. (15th January 2015) - Juadjur, A.; Mohn, C.; Schantz, M.; Baum, M.; Winterhalter, P.; Richling, E.
Highlights: A bilberry extract was submitted to fractionation by solid phase technique. Polymeric, phenolcarbonic acid and anthocyanin rich fractions were achieved. Bilberry extract and fractions were tested for antioxidative properties in vitro . Phenolcarbonic acid rich fraction showed the most potent antioxidative activity. Abstract: The incidence of chronic diseases increases with advancing age of the population. A commonly discussed cause of chronic diseases is oxidative stress, which occurs in the body when there is an imbalance between the formation and inactivation of so-called reactive oxygen species (ROS). Epidemiological data suggest that a 'healthy diet', with a high content of flavonoids indicates preventive properties and correlates with an inverse effect with respect to the risk of chronic diseases. Berries (especially bilberries, Vaccinium myrtillus L.) are an important source of these flavonoids. In this study, we investigated, in vitro, the antioxidative properties of fractions obtained from a commercially available anthocyanin-rich bilberry extract (BE). As markers for antioxidative activity, the intracellularly generated ROS levels, oxidative DNA damage, and total glutathione (tGSH) levels were determined in the human colon cell lines Caco-2 and HT-29. In Caco-2 cells, the ROS levels and, in both cell lines, the oxidative DNA damage, were significantly reduced in the presence of the original BE and phenolcarbonic acid-rich fraction. Total GSH levels were slightly increased after pretreatment with BE, phenolcarbonic acid and the polymeric fractions, but not with the anthocyanin fraction. In summary, the BE and the therefrom-isolated phenolcarbonic acid-rich fraction, showed the most potent antioxidative activity whereas the polymeric and anthocyanin-rich fraction, in total, were less active.